Social Enterpreneurship: Upaya Peningkatan Skill Mahasiswa Teologi dalam Pelayanan Holistik - Iwan Setiawan Tarigan; Arip Surpi Sitompul; Herdiana Boru Hombing; Warseto Freddy Sihombing (LP. Ma'arif Janggan Magetan, 2024)
Today there is an economic gap in the midst of the congregation. The Church must play a role in overcoming the economic problems of the people. That is why the role of the pastor is very strategic, because the church as a whole is driven by the pastor. The purpose of this study is to produce a Christian entrepreneurship module design in an effort to produce quality and effective student skills in realizing holistic service. The type of research used in this study is research and development. The steps used include: potential and problems, data collection, product design, design validation, design revision, product trial, and product revision. Product development carried out in this research only reaches the stage of producing the final product, namely the Christian entrepreneurship module. It can be concluded that: The textbooks produced in this study are developments from various sources; And this research and development produces products in the form of textbooks in the form of textbooks as an effort to improve the skills of theology students in holistic service.